Species Composition of Main Pests of Fig and Bioecology of Important Species (Texas Journal of Agriculture and Biological Sciences, 2024)
The climatic conditions of Uzbekistan are favorable for the cultivation of crops adapted to the subtropical climate. These include figs. These tree-shrubs have been planted since ancient times and have become a branch of horticulture for the countries of Central Asia, including the people of Uzbekistan.